Study of genetic diversity in muskmelon (Cucumis melo) from different horticultural groups - BHIMAPPA, B B; CHOUDHARY, H; BEHERA, T K; SHARMA, V K; HUSSAIN, ZAKIR; TOMAR, B S (The Indian Journal of Agricultural Sciences, 2019)
An experiment was carried out to analyze genetic divergence through multivariate analysis based on D2 and principal component analysis (PCA) for 24 yield contributing traits among 67 muskmelon (Cucumis melo L.) genotypes from 3 horticultural groups. The 67 genotypes were grouped into 15 distinct clusters. Cluster I consisted of 27 exotic lines from inodorous and cantalupensis group followed by cluster XIVwith 14 genotypes. Majority of genotypes of cluster XIV were developed in India except 4 exotic lines. The remaining13 clusters comprised of only 2 genotypes each and thus clustering pattern indicated enough genetic divergence in the germplasm under study. The highest value of intra cluster distance (43. 68) was found for cluster XV with 2 genotypes followed by XIV (38. 35) possessing 14 genotypes and cluster I (31. 07) having 27 genotypes. The highest inter cluster distance was observed between cluster XV and XIV (42. 24), followed by the cluster XV and XI (40. 70) and cluster XV and VI (40. 48). The first 3 principal components accounted for majority (53. 77%) of the total variation. The traits which contributed positively to PC1 were days to first male flower opening, average fruit weight, fruit length, cavity length and yield per plant. The high yielding muskmelon genotypes with better fruit quality traits like DM-31, DM-145, DM-159 and DM-162 from inodorous group of Cluster I and Pusa Madhuras (Cluster VII), Kashi Madhu, Punjab Sunheri, Hara Madhu (Cluster XIV) from cantalupensis group should be utilized for hybrid development between two horticultural groups to incorporate theyield and desirable fruit quality traits from both groups.